2019
DOI: 10.1002/cbin.11121
|View full text |Cite
|
Sign up to set email alerts
|

The induction of ferroptosis by impairing STAT3/Nrf2/GPx4 signaling enhances the sensitivity of osteosarcoma cells to cisplatin

Abstract: Recent studies have indicated that promoting ferroptosis is a promising approach to attenuate drug resistance of cancer cells. Hence, this study aimed to induce ferroptosis in osteosarcoma cells, thereby increasing the sensitivity to cisplatin. Osteosarcoma cells MG63 and Saos-2 were incubated with increasing doses of cisplatin to generate cisplatin-resistant strains, MG63/DDP and Saos-2/DDP. 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) and flow cytometry assays were performed to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
135
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(138 citation statements)
references
References 25 publications
2
135
1
Order By: Relevance
“…The anticancer property of erastin has been proved to be incredibly effective in a variety of cancers, such as liver cancer, lung cancer, gastric cancer, breast cancer, osteosarcoma, etc. (21)(22)(23)(24). Combination therapy of erastin with other chemotherapeutic agents like cisplatin shows a significant synergistic effect in a number of cancers.…”
Section: Introductionmentioning
confidence: 99%
“…The anticancer property of erastin has been proved to be incredibly effective in a variety of cancers, such as liver cancer, lung cancer, gastric cancer, breast cancer, osteosarcoma, etc. (21)(22)(23)(24). Combination therapy of erastin with other chemotherapeutic agents like cisplatin shows a significant synergistic effect in a number of cancers.…”
Section: Introductionmentioning
confidence: 99%
“…[39][40][41] For example, under the stress stimuli, the promotion of ferroptosis by ferroptosis inducer reactivated ferroptosis in osteosarcoma cells and consequently enhanced the sensitivity to cisplatin. 39 According to the earlier observation of Initially, we proved that iron overload could be induced by cisplatin exposure. We employed two assays detecting Fe 2+ : the FerroOrange staining reflects intracellular Fe 2+ and the Mito-FerroGreen staining assesses mitochondrial Fe 2+ , respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidences have indicated that promoting ferroptosis is a promising approach to attenuate drug resistance in cancer chemotherapy [37,38]. Given the therapeutic promise for inducing ferroptosis in drug-resistant cancers, a potent GPX4 inhibitor is paramount [39,40].…”
Section: Discussionmentioning
confidence: 99%